HUKUMAN MATI BAGI PELAKU TINDAK PIDANA KORUPSI (ANALISIS AYAT-AYAT KORUPSI DALAM ALQUR’AN) - Anang Wahyu Setiawan; Almasudah Almasudah; Hadi Nasroh (JAS : Jurnal Ahwal Syakhshiyyah, 2022)
This research aims to explore Wahbah Zuhaylî 's view of the death penalty for corruptors. The focus of this research is Wahbah Zuhaylî 's interpretation in his al-Tafsîr al-Munîr fî al-Aqîdah wa al-Sharî'ah wa al-Manhaj, particularly on the verses of corruption in the terms of sariqah, risywah, and khiyânah. This type of research is qualitative and library research in the field of Ulûm al-Qur'an and Ulûm al-Tafsîr. The method used is thematic analytic (al-Tahlîli al-maudhû'i). The results of this research are indicated that the sariqah, risywah, and khiyânah according to Zuhaylî  is a form of violation that is very dangerous and acted upon. The effect of corruption has more dangerous effects than murder. The law of cutting hands (qat’u al-yad) for those who are definitely guilty is a form of preventive action and learning. The death of penalty in the those three terms is not explicitly stated by him. Even so, it does not mean that it cannot be done, because it can still use the ta'zir process. With the ta'zir, the court or judge possible to increase the penalty status from qat’u al-yad into a death punishment if the conditions is fulfilled.Key words: qat’u al-yad, death penalty, sariqah, risywah, khiyânah